The Impact Of Changes In Accounting Standards On The Quality Of Corporate Financial Reports - Aulia Rahman Mehaga Sembiring; Leon Reynold Pakpahan; Fitri Yani Panggabean (INFOKUM, 2025)
This study examines the impact of changes in accounting standards on the quality of corporate financial reports. Accounting standards play a crucial role in ensuring transparency, consistency, and comparability in financial reporting, which is essential for investors, regulators, and other stakeholders in making informed decisions. However, frequent revisions and updates to these standards may create challenges for companies in maintaining compliance while ensuring accurate financial representation. Using a quantitative approach, this study analysed financial data from selected companies before and after significant accounting standard changes. Key financial indicators such as earnings quality, revenue recognition, asset valuation, and disclosure levels are evaluated to determine the extent to which these changes influence financial reporting. Multiple regression analysis is used to assess the relationship between accounting standard updates and financial report quality. The findings reveal that changes in accounting standards have a significant impact on financial reporting quality. Improved disclosure requirements and fair value measurement enhance transparency and reliability, while frequent changes may lead to temporary inconsistencies and increased compliance costs. Additionally, companies with strong internal controls and corporate governance tend to adapt better to new standards, ensuring higher financial reporting quality. This study provides valuable insights for corporate managers, auditors, investors, and policymakers, highlighting the importance of effective implementation strategies to minimize disruptions while improving financial report accuracy. Strengthening accounting regulations and providing adequate transition periods can enhance the overall quality of financial reporting in response to evolving standards.